PARTISIPASI MASYARAKAT DALAM PELAKSANAAN PROGRAM BADAN USAHA MILIK DESA DAMAI KABUPATEN SIDENRENG RAPPANG - Riska Jabir; Andi Astinah Adnan; Muhammad Ikbal; Nurjannah Nonci (JIA: Jurnal Ilmiah Administrasi, 2022)
This study aims to determine community participation in the implementation of the Village Owned Enterprise program in Damai Village, Watang Sidenreng District, Sidenreng Rappang Regency. The population in this study was 476 head of family in Damai Village, Watang Sidenreng District, Sidenreng Rappang Regency with a sample of 74 people. This type of research is descriptive quantitative. Data collection techni 48 ques used in this study were observation, questionnaires, and literature study. The data analysis technique used is the IBM SPSS statistic 21.0. The results of this study indicate that Community Participation is 62.8% in good category with ideal results 62.91% from 100% expected, the factors that influence community participation in implementing village-owned enterprise programs in Damai Village, Watang Sidenreng District, Sidenreng Regency Rappang includes motivation 36%, knowledge 43%, individual experience 21.3%, role of stakeholders 37.3%, social conditions 19.5%, political conditions 16.6%, economic conditions 26%, and cultural conditions 27.6%